2016
DOI: 10.1111/jan.13204
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of measurement properties of self‐reported instruments for evaluating self‐care in adults

Abstract: Despite the development of several instruments to assess self-care in the adult population, no instrument can be fully recommended to clinical nurses and researchers. Further studies of high methodological quality are needed to confirm the measurement properties of these instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 41 publications
(161 reference statements)
3
40
0
5
Order By: Relevance
“…The aim of this study was to validate the SASE‐I in a sample of adults aged 65 and older. The SASE was selected among other self‐care instruments as it showed good psychometric properties in previous studies . Our findings showed the SASE‐I has good validity and reliability, but partially differs from the SASE‐S.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The aim of this study was to validate the SASE‐I in a sample of adults aged 65 and older. The SASE was selected among other self‐care instruments as it showed good psychometric properties in previous studies . Our findings showed the SASE‐I has good validity and reliability, but partially differs from the SASE‐S.…”
Section: Discussionmentioning
confidence: 80%
“…Although several instruments are available to assess self‐care in the general population, only three self‐report instruments have been developed specifically for the healthy elderly population : Lorensen's Self‐Care Capability Scale , the Self‐care of Home‐dwelling Elderly instrument and the Self‐care Ability Scale for the Elderly (SASE) . Researchers developed these instruments in Scandinavian countries, showing the interest these countries have regarding self‐care in the ageing process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is no single criterion in the selection of the instruments. Nurses and researchers should decide which instrument is best for assessing on the basis of the purpose of the study, research approach (Streiner & Kottner, 2014;Urpí-Fernández et al, 2017) and evidence shown by specific measurement properties to be important for a particular condition or population (Matarese, Lommi, & De Marinis, 2017). such as measurement error and responsiveness, was found.…”
Section: Discussionmentioning
confidence: 99%